A Finansial Distress Prediction Using The Altman, Springate, Zmijewski, and Grover Models in Pharmaceutical Companies Listed on Indonesia Stock Exchange - Gustirani , Indri; Fathia Farahnash,; Haddan Dongoran,; Nuryadin, usmin; Teguh Wiharko, (Adpebi Science Series, 2024)
The goal of this research is to determine: (1) whether or not the outcomes of the Altman, Springate, Grover, and Zmijeski models for financial distress prediction differ from one another; (2) Which model is the most accurate at identifying financial distress in Indonesian pharmaceutical companies. A comparison of the four forecasting models shows that each model's precision is according to the firm's actual situation. Corporate financial reports posted on the Indonesian Stock Exchange (IDX) website were the source of the data for this research.This research focused on pharmaceutical’s companies a list from 2016 to 2018, the Indonesian Stock Exchange (IDX). Purposive sampling was used for the sampling, and eight businesses were chosen as research samples. Data analysis technology uses parametric statistical tests, namely paired samples t-test and prediction model accuracy tests, provided that the data must be normally distributed. This research uses descriptive statistical methods, normality tests, and matched samples to assess the results of four financial distress prediction models and T-test sample analysis methods utilizing the SPSS program. The results of this research show that there are significant differences in the ability of the Altman, Springate, Grover, and Zmijewski models to predict financial distress. The Springate model has a 91.67% accuracy rate, which is the highest